Mini Sharing Pemanfaatan Media Quiz Online bagi MGMP Guru Biologi Sidoarjo berbasis Edmodo - Yuwono Marta Dinata; Hebert Adrianto; Hanna Tabita Hasianna Silitonga; Iman Pasu Marganda Hadiarto Purba (Journal of Appropriate Technology for Community Services, 2021)
This mini-sharing activity was organized by the Faculty of Information Technology, Ciputra University Surabaya in collaboration with the Faculty of Medicine, Ciputra University and the Faculty of Social Sciences and Law, State University of Surabaya. This training was conducted during the Covid-19 pandemic. This training is given to Musyawarah Guru Mata Pelajaran (MGMP) group, especially Biology subjects because Biology Teachers need support for the use of online media in teaching, especially during this pandemi. Through MGMP group this activity was intended to reach not only one school but more schools so that it is will be expected to have a wider impact. Based on the results of the discussion, there are teachers who are not used to using online media, especially in terms of assessments through online quiz media for their students. After participating in this mini sharing, the teachers can immediately put the knowledge they have learned because this training was done using the hands-on method. Through mini sharing, teachers can get alternatives to use technology, Edmodo.